TMJ Ankylosis: Multidisciplinary Approach of Treatment for Dentofacial Enhancement-A Case Report - Pavankumar Janardan Vibhute; Nitin Bhola; Rajiv M. Borle (Hindawi Limited, 2011)
This report describes the multidisciplinary phasewise treatment of a 20-year-old female patient having unilateral right TMJ bony (true) ankylosis whose mouth opening was restricted to 2 mm and mandibular retrognathism; additionally, she was also suffering from speech problems, snoring, difficulty in breathing, and low level of self-esteem and self-confidence. Bilateral gap arthroplasty and temporalis myofascial graft interpositioning through preauricular approach were done in surgical phase followed by the aggressive jaw physiotherapy in postsurgical period. Oral prophylaxis and restorations were followed by the fixed orthodontic therapy to resolve bimaxillary protrusion. Advancement sliding genioplasty was performed to enhance the chin button. Speech therapy and psychological counseling were also performed from time to time to boost up the self-esteem and self-confidence. At the end of treatment, facial esthetics was improved considerably and patient got over the impact of disfigurement, impaired functions, and psychosocial stigma. Rationale to use the multidisciplinary team approach in treatment of such cases is discussed.